A Novel Paradigm in Dentistry- Stem Cell Therapy: A Comprehensive Review - Singh , Shivangi; Puri , Nidhi; Ahuja , Upasana Sethi; Dhillon, Manu; Rathore , Akshay; Ahuja , Seema; Puri, Nidhi (International Journal of Psychosocial Rehabilitation, 2020)
Stem cells have the capability to influence the millions of lives by offering unparalleled possibilities for emerging new medical therapies for crippling and terminal diseases and a new way to explore essentials of biology, making a template for cell-based therapies. These unique cells have remarkable potential of endless self-renewal and differentiation into numerous cell types. Every new cell in turn can either remain as a stem cell or get differentiated to emerge into a new cell with more specialized function e.g a muscle cell, brain cell or red blood cell. Recent literature has targeted the use of several stem cells extracted extraoral and intra orally that can be applied in regenerative dentistry; posing numerous potential therapeutic applications. This leads us to the cutting edge of stem cell research as it has numerous applications in dentistry. An innovative perspective for the application of stem cells in multifaceted dentistry requires detailed planning and comprehensive research work. It is the need of the hour to shift from corrective dentistry to preventive and regenerative dentistry. Thus, this review emphasizes on characteristic properties, challenges and current research, along with new avenues and prospects of stem cells in dentistry and in management of oral mucosal lesions.